Pengaruh Tingkat Pengungkapan Corporate Social Responsibility Terhadap Information Asymmetry Dengan Variabel Market Share dan EPS Growth Di Perusahaan Terbuka Indonesia - Margaret Carolina; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
The affect of Corporate Social Responsibility on information asymmetry still rarely done previous researchers, majority were to examine the relationship between Corporate Social Responsibility with financial performance. This study aimed to examine the affect of level corporate social responsibility (CSR) disclosure to the information asymmetry. The level of disclosure of corporate social responsibility was measured by using The Sustainability Reporting Index guidliness that valued by the criteria of the GRI. While the information asymmetry was measured by using the bid-ask data. The result showed that there was positive significant correlation of corporate social responsibility disclosure on bid-ask spread. The result also showed that growth in EPS (EPS Growth) had no affect on bid-ask spread, while market share had negative significant effect on bid-ask spread.